Inovasi Kewirausahaan Buket Dalam Meningkatkan Ekonomi Kreatif di IPPNU Desa Rowolaku - Mareta, Feby Muli (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
The study analyzes how bouquet-based entrepreneurship initiated by the Nahdlatul Ulama Female Students Association (IPPNU) in Rowolaku Village strengthens the local creative economy and members’ economic independence. Using a Participatory Action Research (PAR) approach, IPPNU members were actively involved in needs assessment, program planning, training implementation, and reflection. Through coordination with village authorities, hands-on training in flower and snack bouquet production, and digital marketing via social media, the program succeeded in improving entrepreneurial skills and establishing a small creative business unit that generates income for organizational activities. The process also enhanced solidarity, ownership, and self-confidence among young women, demonstrating the relevance of PAR-based creative entrepreneurship for youth and women’s empowerment in rural communities.